Europeans as Coastal Brokers in the West and West-Central African Slave Trade (1680-1720) - Guarda, Maria Inês Godinho (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
The years between 1680 and 1720 saw the intensification of the regional slave trade in West Africa. Previous scholarship has focused almost exclusively on Africans and Afro-descendants as brokers in the region, placing Europeans as Atlantic intermediaries. Europeans as Coastal Brokers in the West and West-Central African Slave Trade (1680-1720) argues that not only was European mediation in Africa deeply interwoven with endogenous trade networks, but also that it was eagerly desired by the powerful potentates of the hinterland as a means of increasing their political and economic power over the region. Examining the interconnected interests of coastal authorities and Europeans, this book demonstrates that Europeans were the key brokers in the diversification of slave trade routes to the shore.